The image of hope in the work of Matnazar Abdulhakim - Mohichehra Rustamova (Zien Journals, 2022)
Only when people hope can they have a beautiful smile, endure trials, and endure hardships. Matnazar Abdulhakim also introduces the image of hope in poetry, saying that one should live with hope at all times.
Keywords: Hope; confidence; longing; serenity